Experimental and theoretical analysis of fatigue properties of liner for the large pressure equipment - Feng Xianzhang; Cheng Junwei; Cui Yanme; Jiang Zhiqiang (Functional Materials, 2016)
In order to analyze the working status of the key components of large-width device online, taking liners force status as the object of study before and after reformation of the liners. Specifications for the slab: 230mmx1300mmx2600mm, the initial temperature is 1020 °C, the amount of lateral pressure is 228mm, and the angle of the die is 12°. Using the main tool of frequency fatigue testing machine with the model of PLG-100C, based on the principle of up and down, and it can obtain the distribution rulers of testing and experimental by the method of directly stick the strain chip on the liners. The result of study indicates that it can provide the theoretical basis for the reformation of the liner and the analysis of stress state of large the lateral pressure equipment.